Preliminary studies on optimal plant populations and spacing for cucumber ( Cucumis sativus L.) at Pelotas, Rio Grande do Sul - Garcia, Alseny; Santos, Alverides Machado dos (Pesquisa Agropecuaria Brasileira, 2014)
An experiment to determine optimal spacing within the row and plant density per hill for pickling cucumbers was carried out at Pelotas, Rio Grande do Sul, in 1970. Maintaining a constant row width of 1 m, spacings of 20, 40, and 60 cm between hills and populations of one, two, and three plants per hill were tested in a randomized complete block design, using the variety Chicago Picking, the most popular in the region. A spacing of 40 cm between hills with three plants per hill resulted in the greatest number of fruits of acceptable size per hectare.